EXOTIC WOMEN: UNRAVELLING AESTHETICIZATION AND OBJECTIFICATION IN HEERAMANDI - Megha Pratheep; Devi K (International Journal of Research -GRANTHAALAYAH, 2025)
This paper examines how the tawaifs are portrayed in Sanjay Leela Bhansali's series, Heeramandi: The Diamond Bazaar. It focuses on their representation as objectified figures within the narrative under the pretence of depicting them as women with agency. It examines the colonialist portrayal of courtesans of India by exploring how the film reflects the fantasies of the West about the exotic Indian women by using opulent visuals and patriarchal themes. This study focuses on the cinematic styles used by Bhansali, such as the use of luxurious sets, sparkling costumes, poignant music and other cinematic elements which together contribute to the film's splendour while maintaining a certain image of the East. Furthermore, the paper explores the historical context of the tawaif culture, drawing parallels between their representation in Heeramandi and their roles in historical narratives. The study employs Laura Mulvey’s concept of the Male gaze to critique how Heeramandi constructs an objectified and spectacle-driven narrative of tawaifs. It also examines how Bhansali blurs out the historical realities of tawaifs in this series and uses the same traditional portrayal for global appeal. Additionally, the paper explores the paradox of gender in the portrayal of tawaifs. It looks into the audience's perception of these portrayals and also on the social and cultural impacts. Thus, through this analysis, the paper aims to conduct a critical study to understand how the series contributes to the discussion of gender and identity politics.